Navigating Faith and Feminism: Islami.co’s Countering-Narrative to Anti-feminism Discourses in Indonesia - Siswanti, Hanifa Paramitha; Eni Maryani; Ute Lies Siti Khadijah (DINIKA : Academic Journal of Islamic Studies, 2023)
Anti-feminism is a movement that is more opposed to reaffirming, maintaining, and increasing the subordination of women by patriarchal forces. For this movement, feminist thinking can lead to deviant actions because these thoughts are not in accordance with religious teachings. The group then uses digital media channels to create anti-feminism narratives which are published on Islamic faith-based information websites. The purpose of this study is to reveal how the representation of feminism in Islami.co media acts as a counter-narrative against anti-feminism discourse echoed by other Islamic groups. This study uses a qualitative descriptive approach. The data collection technique was a literature study of documents from various references and the results of media analysis of Islami.co. The data analysis method used is the framing analysis model of William Gamson and Andre Modgliani which is elaborated with the perspective of Representation Theory by Stuart Hall. The result of the study shows that Islami.co is a digital media counter-narratives against anti-feminist discourse. The representation of feminism in this media is interpreted as part of the struggle of Islam in forming the spirit of justice for all mankind. Islami.co packs facts and clarifies the counter-narrative of anti-feminism discourse through authentic sources such as the Qur’an and hadith as well as various arguments that rely on empirical data. This effort is not just for creating justice and equality, but also as a form of obedience to what is commanded by Islam.